Cover Image. (June 2017) - Natto, Zuhair S.; Parashis, Andreas; Steffensen, Bjorn; Ganguly, Rumpa; Finkelman, Matthew D.; Jeong, Y. Natalie
Abstract : The cover image, by Zuhair S. Natto et al ., is based on the Randomized Clinical Trial Efficacy of collagen matrix seal and collagen sponge on ridge preservation in combination with bone allograft: A randomized controlled clinical trial, DOI:10.1111/jcpe.12722 .